Relating Lexical and Syntactic Knowledge to Academic English Listening: The Importance of Construct Representation - Cai, Hongwen (Frontiers in Psychology, 2020)
This study aims to resolve contradictory conclusions on the relative importance of lexical and syntactic knowledge in second language (L2) listening with evidence from academic English. It was hypothesized that when lexical and syntactic knowledge is measured in auditory receptive tasks contextualized in natural discourse, the measures will be more relevant to L2 listening, so that both lexical and syntactic knowledge will have unique contributions to L2 listening. To test this hypothesis, a quantitative study was designed, in which lexical and syntactic knowledge was measured via partial dictation, an auditory receptive task contextualized in a discourse context. Academic English listening was measured via a retired IELTS listening test. A group of 258 college-level native Chinese learners of English completed these tasks. Pearson correlations showed that both lexical and syntactic measures correlated strongly with English listening (r = 0.77 and r = 0.67 respectively). Hierarchical regression analyses showed that both measures jointly explained 62% of the variance in the listening score and that each measure had its unique contribution. These results demonstrated the importance of considering construct representation substantially and using measures that well reflect constructs in practical research.